2022
DOI: 10.3389/fevo.2022.895906
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Potential Invasion Risk of Oryctes monoceros Worldwide

Abstract: As a significant threat to agriculture, pests have caused a great disservice to crop production and food security. Understanding the mechanisms of pests’ outbreaks and invasion is critical in giving sound suggestions on their control and prevention strategies. The African rhinoceros beetle, Oryctes monoceros (Olivier), as the most damaging pest of palms, banana, sugarcane, and pineapple, severely threatens their production due to its ability to kill both young and matured hosts. Analyzing the effect of climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Apart from the intrinsic questions related to the large-scale monoculture of a single plant species over extensive areas, it should be noted that global palm oil production is limited Àin its vast majority-to a rather narrow geographical region that is virtually restricted to either side of the Strait of Malacca. This concentration might lead to serious problems should either an extreme climate event or a pest/disease invasion arises, which could be interconnected (Paterson, 2019;Paterson et al, 2013;Aidoo et al, 2022).…”
Section: Highlightmentioning
confidence: 99%
“…Apart from the intrinsic questions related to the large-scale monoculture of a single plant species over extensive areas, it should be noted that global palm oil production is limited Àin its vast majority-to a rather narrow geographical region that is virtually restricted to either side of the Strait of Malacca. This concentration might lead to serious problems should either an extreme climate event or a pest/disease invasion arises, which could be interconnected (Paterson, 2019;Paterson et al, 2013;Aidoo et al, 2022).…”
Section: Highlightmentioning
confidence: 99%
“…Though consuming edible insects for food and using them for treating animal and human diseases have received greater attention, there needs to be more information on other benefits associated with production, marketing and harvesting. For instance, the African coconut beetle Oryctes monoceros (Olivier), Asiatic rhinoceros beetles Oryctes rhinoceros (Linnaeus), and African palm weevil Rhychophorus phoenicis (L.) attack and kill economically important crops, such as palms, banana, and pineapple (17)(18)(19)(20). However, many people in Sub-Saharan Africa consume the same insects because of their nutritional properties (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean region, studies have reported the invasion of new pests causing multiple outbreaks with severe socioeconomic impacts [32][33][34][35]. Studies have argued that recent pest outbreaks were fostered by climate change [36][37][38], which suggests that future scenarios of climate warming might exacerbate the number of outbreaks on crop fields [38]. Therefore, understanding how agro-ecosystems are influenced by the combined impacts of abiotic and biotic stressors is vital for maintaining food security and nutrition.…”
Section: Introductionmentioning
confidence: 99%